Mothering for Schooling - Griffith, Alison I. (Education Policy Analysis Archives, 1995)
In this paper I explore the relationship between mothering work in the family and the social organization of schooling. In particular, I address the ways in which mothers coordinate and contest the textually-organized discourse of schooling In contrast to other studies of the family/school relationship, this research began in the experience of mothers whose children attend primary school. The data were collected through interviews with mothers in two cities in Ontario. Mothering work constructs families that are differently connected to schools – a connection strongly shaped by and constitutive of social class.